The role of antique heritage in sculpture and graphic works by Aristide Maillol - Mishchuk, Anna Yu. (Actual Problems of Theory and History of Art, 2012)
The classical myths were favorite subjects for all sculptors since antiquity till today. Aristide Maillol in his artistic intentions concentrates on beauty and harmony of the naked female body. We can find some parallels between his works and antique statues, but A. Maillol never tended to stylization or synthesis. He took motifs from nature and added his own artistic vision, “completing” the nature. The most important point for him was comprehension of methods of the Greek masters, but not copying them.
Keywords: Aristide Maillol; monumental sculpture; terracotta; book graphics; antique motifs